CORRUPTION PREVENTION FOR STUDENTS IN TAKALAR DISTRICT DUSTURIYAH SIYASAH PERSPECTIVE - Abdul Basir, Ahmad Farhan Mandang (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
This study discusses Corruption Prevention for Students in Takalar District from the Siyasah Dusturiyah Perspective. The formulation of the problem in this research is how are the stages of corruption prevention for students in Madrasah Aliyah Bulukunyi, Takalar Regency, and what are the forms of corruption prevention for students at Madrasah Aliyah Bulukunyi, in Takalar Regency, Siyasah Dusturiyah Perspective.This research is a qualitative research which is located in Madrasah Aliyah Bulukunyi school. The data sources for this research were the Head of Madrasah, Deputy Head of Student Affairs, Deputy Head of Public Relations, Teachers, Youth Leaders, Religious Leaders and Students of Madrasah Aliyah Bulukunyi in Takalar Regency. Data collection techniques through observation, interviews and documentation. The data processing and analysis techniques used include word reduction, data presentation and drawing conclusions. The results of this study indicate that: Stages and Forms of Corruption Prevention for Students in Madrasah Aliyah Bulukunyi Takalar Regency have begun to be implemented in accordance with the Regulations of the Ministry of Religion concerning the Decree of the Director General of Islamic Education Regarding Guidelines for Implementing Anti-Corruption Education in Madrasas and the Regulation of the Takalar Regent No. 22 of 2022 concerning Anti-corruption Education.